2010
DOI: 10.1097/hp.0b013e3181b8ce81
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Smoking in the Radon-Related Lung Cancer Risk Among German Uranium Miners: Results of a Nested Case-Control Study

Abstract: The possible confounding effect of smoking on radon-associated risk for lung cancer mortality was investigated in a case-control study nested in the cohort of German uranium miners. The study included 704 miners who died of lung cancer and 1,398 controls matched individually for birth year and attained age. Smoking status was reconstructed from questionnaires and records from the mining company's health archives for 421 cases and 620 controls. Data on radon exposure were taken from a job-exposure matrix. Smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…Unfortunately, only very limited and incomplete data on smoking exist in the full cohort that could not be used. In a nested case-control study on lung cancer,33 it was shown that most Wismut miners were smokers and adjustment for smoking only marginally reduced the radon-related lung cancer risk. Smoking was broadly categorised into non-smokers defined as lifetime non-smokers or ex-smokers since 20 years or smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only very limited and incomplete data on smoking exist in the full cohort that could not be used. In a nested case-control study on lung cancer,33 it was shown that most Wismut miners were smokers and adjustment for smoking only marginally reduced the radon-related lung cancer risk. Smoking was broadly categorised into non-smokers defined as lifetime non-smokers or ex-smokers since 20 years or smokers.…”
Section: Discussionmentioning
confidence: 99%
“…This high-socioeconomic homogeneity of the cohort should limit potential confounding associated with lifestyle factors. Furthermore, in a nested case–control study on lung cancer among Wismut miners, it could be demonstrated that nearly all miners were smokers and that the correlation with radon exposure was low 46. Another limitation is the potential misclassification of death certificates, missing information on subtypes and cancer incidence data.…”
Section: Discussionmentioning
confidence: 99%
“…Individual data on smoking are only available for 38% of the cohort members. A case-control study on lung cancer nested in the WISMUT cohort exhibited no indication of major confounding by smoking on the radon-related lung cancer risk 41. Given that smoking is a much stronger risk factor for lung cancer than leukaemia, it is unlikely that smoking is confounding the radiation-related leukaemia risk.…”
Section: Discussionmentioning
confidence: 98%